The political economy of Cambodia's transition, 1991-2001 - Hughes, Caroline (London ; New York : RoutledgeCurzon, 2003)
Cambodia underwent a triple transition in the 1990s: from war to peace, from communism to electoral democracy, and from command economy to free market. This book addresses the political economy of these transitions.
Contents; Acknowledgements; Note; 1 Introduction: points of departure; 2 Economy and state ... society relations; 3 Economic reform and state-making in the 1990s; 4 State and party in the 1990s; 5 International intervention and international community'; 6 Multi-party politics in the 1990s; 7 Promoting democracy: NGOs and civil society'; 8 Urban protest movements: the future of Cambodian democracy; 9 Conclusion: manipulating Cambodia's transitions; Notes; Sources; Index.
Includes bibliographical references (p. [245]-254) and index.
Keywords: Cambodia -- Economic conditions; Cambodia -- Politics and government -- 1979-